Day One Drain Amylase as a Predictor of Postoperative Pancreatic Fistula Following Pancreaticoduodenectomy - Pradhan, Sumita; Kandel, Bishnu; Bhandari, Ramesh Singh; Joshi Lakhey, Paleswan (Journal of Nepal Health Research Council, 2023)
Background: Postoperative pancreatic fistula remains the most challenging complication following pancreaticoduodenectomy. As per the definition by the International Study Group on Pancreatic Fistula, post operative pancreatic fistula is diagnosed on or after postoperative day 3. However, several studies have demonstrated that drain fluid amylase on postoperative day 1 may be a better predictor. This study was conducted to determine the diagnostic value of day one drain amylase in predicting the development of post-operative pancreatic fistula.Methods: This was a prospective observational study of patients, who underwent pancreaticoduodenectomy between April 2016 and May 2017. Post operative pancreatic fistula was defined by the International Study Group on Pancreatic Fistula (2005) criteria. The diagnostic value of day one drain amylase was determined by doing a receiver operating curve analysis and compared with the postoperative day 3 value.Results: A total of 49 patients were included. Post operative pancreatic fistula developed in 28 patients (Grade A - 40.8%; B - 12.2%; C - 4.1%). Receiver operating curve analysis confirmed the predictive relationship of day one drain amylase with an area under the curve of 0.79 and kappa 0.5. For clinically relevant postoperative pancreatic fistula, day 3 drain amylase was the better predictor (AUC for DFA3 was 0.73 while AUC for DFA1 was 0.51). A day one drain amylase cut-off value of 350 U/L demonstrated a sensitivity of 75% and specificity of 77.8% with an accuracy of 76.2%. Conclusions: Day one drain amylase predicts postoperative pancreatic fistula in patients following pancreaticoduodenectomy but for clinically relevant postoperative pancreatic fistula, day three drain amylase is a better predictor.Keywords: Amylase; drain fluid amylase; pancreaticoduodenectomy; Pancreatic fistula